Комплексные исследования теплогидравлического совершенства рекуперативных теплообменников - Сорока, Б.С.; Воробьев, Н.В.; Кудрявцев, В.С.; Письменный, А.С. (Энерготехнологии и ресурсосбережение, 2014)
Представлены результаты сопоставительных экспериментальных исследований теплообмена и аэродинамики в высокотемпературных рекуператорах авторской и альтернативных конструкций. Исследования проводились на огневом стенде с целью сравнения характеристик опытных секций BD гладкотрубных петлевых рекуператоров и образцов с интенсификаторами теплообмена различной геометрии: 1) конструкций SP1 и SP2 со спиральными вставками двух типов, установленными по всей длине теплообменных труб (относительный шаг спиралей σ₁ = s₁/d = 4,0 и σ₂ = s₂/d = 2,5 соответственно). Такие рекуператоры соответствуют существующим зарубежным аналогам; 2) конструкции MD3 авторской разработки с гибкими крестообразными вставками — вторичными излучателями, установленными по всей длине теплообменных труб. Определены теплотехнические и теплогидравлические преимущества предложенных рекуператоров типа MD3 по сравнению с зарубежными конструкциями со спиральными вставками-турбулизаторами и традиционными отечественными гладкотрубными рекуператорами. Представлено результати порівняльних експериментальних досліджень теплообміну та аеродинаміки у високотемпературних рекуператорах авторської та альтернативних конструкцій. Дослідження проводилися на вогневому стенді з метою порівняння характеристик дослідних секцій BD гладкотрубних петльових рекуператорів та зразків з інтенсифікаторами теплообміну різної геометрії: 1) конструкцій SP1 та SP2 зі спіральними вставками двох типів, встановленими по всій довжині теплообмінних труб (відносний крок спіралей σ₁ = s₁/d = 4,0 та σ₂ = s₂/d = 2,5 відповідно). Такі рекуператори відповідають існуючим закордонним аналогам; 2) конструкції MD3 авторської розробки з гнучкими хрестоподібними вставками — вторинними випромінювачами, встановленими по всій довжині теплообмінних труб. Визначено теплотехнічні та теплогідравлічні переваги запропонованих рекуператорів типу MD3 у порівнянні із зарубіжними конструкціями зі спіральними вставками-турбулізаторами та традиційними вітчизняними гладкотрубний рекуператорами. In frame of the presented work the results of comparative experimental investigations carried out on heat transfer and fluid dynamics processes within high temperature recuperators of the authors’ and alternative designs are discussed. The researches were fulfilled at firing rig with a purpose of comparison the characteristics of the test sections of smooth tube recuperator (BD) and the specimens with the facilities of different geometry providing heat transfer intensification: 1) the designs SP1 and SP2 with the spiral inserts of two types installed by the whole length of heat exchange tubes with the relative pitch of the spirals σ₁ = s₁/d = 4,0 and σ₂ = s₂/d = 2,5 respectively. These recuperators meet the existing foreign analogous prototypes; 2) design MD3 of authors’ design with flexible cross-shaped inserts — the secondary emitters installed by the whole length of heat-exchange tubes. The heat engineering and combined heat and hydraulic advantages of proposed recuperators of MD3 type in comparison with the foreign designs with the spiral inserts-turbolators and with traditional native smooth-tube recuperators (BD) have been identified. It has been stated that especially appreciable results of the tests make the advantages of MD3 design regarding the most representative temperature criterion — temperature difference D`Tw-a between the tube walls and of an air flow. This value for authors’ design is decreased approximately 4 times in comparison with BD design and more than 2 times lower in comparison with that for foreign designs SP1 and SP2.